Comprehensive Reconnoitre of Ichthyofauna in the Trans Himalayan Region of Jammu and Kashmir and Ladakh: A Detailed Checklist, Threats and Conservation Measures - Zaheer Abass; Tasaduq Hussain Shah; Farooz Ahmad Bhat; Karankumar Kishorkumar Ramteke; Ishrat Mohd; Naila M. Bhat; Inab Majeed Bala; Junaid Ahmad Khan; Rinkesh Nemichand Wanjari (Journal of Indian Fisheries Association, 2024)
This study aims to collect a comprehensive list of fish species inhabiting the trans-Himalayan region of Jammu & Kashmir and Ladakh. A survey of published literature and field sampling on fish distribution in the trans Himalayan region revealed 130 fish species belonging to 10 orders, 23 families, and 58 genera. Among these species, most fish species were classified as Least Concern. However, 2 endemic hill stream fish species were identified as Critically Endangered namely (Triplophysa kashmirensis and Glyptothorax kashmirensis). The study emphasizes the IUCN conservation status of these species and proposes management strategies for their conservation and sustainable management. The study highlights the importance of understanding fish diversity, distribution patterns, and habitat preferences in devising effective conservation measures. The region's unique biotic zones and abundant cold-water resources make it a significant habitat for freshwater fishes. Studies on fish species in the trans-Himalayan region, especially in Jammu & Kashmir and Ladakh, are still inadequate. This study aims to compile a detailed inventory of fish species in this region. The study also emphasizes the need for comprehensive research and conservation efforts to address the alarming decline of riverine fish resources in the trans-Himalayan region.